Pengaruh Intensitas Komunikasi Orang Tua Terhadap Motivasi Belajar Anak (Studi Pada Masyarakat Desa Fiditan, Kecamatan Dullah Utara, Kota Tual) - Latar, Jumila (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
This research is driven by the observation of low learning motivation among children, attributed to suboptimal parental communication during their learning process, which has resulted in decreased academic achievement. The research problem formulated in this study is whether there is a relationship between the intensity of parental communication and children's learning motivation at home. The objective of this study is to determine the significance of the relationship between the intensity of parental communication and children's learning motivation at home. The theoretical framework of the study is based on Devito's theory of interpersonal communication and Djamarah's theory of motivation. A quantitative research method was employed to measure the significance of the relationship between the intensity of parental communication and children's learning motivation. Data were collected through primary sources, specifically questionnaires, and secondary sources, including literature, documents, and archives. This research was conducted in Fiditan Village, South Dullah District, Tual City.